A transient characteristic-based balancing method of rotor system without trail weights. (1st February 2021) - Zhao, Shibo; Ren, Xingmin; Deng, Wangqun; Lu, Kuan; Yang, Yongfeng; Fu, Chao
Highlights: The transient equation of rotor system is derived by the transfer matrix method. Experiment is carried out on the general rotor system. A transient characteristic-based balancing method (TCBM) is proposed. The rotor system is balanced by transient responses without trail weights start-up. The efficiency of the TCBM is verified by simulations and experiments. Abstract: In this paper, a transient characteristic-based balancing method (TCBM) combined with dynamic load identification (DLI) technique to identify the unbalance parameters of the general rotor system is proposed. The dynamical equations of motion of general rotor system is derived by the transfer matrix method (TMM). Then the DLI technique is used to obtain the transient excitation forces, which are totally estimated by the transient vibration responses and the modal characteristics of the rotor system. Theoretical error analyses are carried out to verify the accuracy of the calculated results of the transient excitation forces and the validity of the DLI technique. The unbalance parameters are identified by calculating the results of the transient excitation forces with unbalance characteristic points. The numerical and experimental results demonstrate that the proposed method has good performance in dynamic balancing of the rotor system. The dynamic balancing accuracy of the TCBM is close to the influence coefficients method (ICM) in experimental investigations, while the TCBM balancing through transient vibration responses and without trail weights. More importantly, it will facilitate the on-site dynamic balancing process by designing a complete set of balancing system tools for rotor dynamics analysts based on the TCBM.